REVITALISASI SISTEM PENGELOLAAN REKAM MEDIS DI KLINIK KHALIFAH KABUPATEN TANGERANG TAHUN 2019 - Rumana, Nanda Aula; Widjaya, Lily; Indawati, Laela; Sitoayu, Laras; Kusumaningtiar, Devi Angeliana (Universitas Esa Unggul, 2020)
AbstrakThe clinic is a health care facility that provides basic and specialist services. Clinical obligation in providing services including organizing medical records. Medical record data can be used as a guide for examination of patients, improving the quality of services, education and research, determining funding, health statistics material, and proving legal, disciplinary and ethical issues. Organizing medical records in a health service consisting of patient registration, data processing of medical records, auditing the contents of medical records, archiving / managing medical records and presenting medical record information. Poor management of medical records can cause poor service quality. Klinik Khalifah is a private clinic that serves 24 hours of childbirth treatment, managed by individual which is located in Teluk Naga, Tangerang District, Banten. The purpose of this service is to revitalize the medical record management system at the Klinik Khalifah, namely by determining and creating a numbering system, naming system, storage system and medical record alignment system that is effective and efficient. Based on the results of community service revitalization of the medical record management system at the Klinik Khalifah, between a decentralized filing system that turns into centralization, a registered process becomes electronic, a numbering system with a 6 digit numbering system unit, the numbering system can be used for family numbering, the naming system (according to the ID card), the alignment system from the direct number to the submission of terminal digits / final number system.Ã‚Â Keywords: management, medical records, clinicsÃ‚Â AbstractKlinik merupakan fasilitas pelayanan kesehatan yang menyediakan pelayanan dasar dan spesialistik. kewajiban klinik dalam memberikan pelayanan diantaranya menyelenggarakan rekam medis. Data rekam medis dapat digunakan sebagai petunjuk untuk pemeriksaan pasien, peningkatan kualitas pelayanan, pendidikan dan penelitian, menetapkan pembiayaan, bahan statistik kesehatan, serta pembuktian masalah hukum, disiplin dan etik. Penyelengaraan rekam medis dalam sebuah pelayanan kesehatan terdiri dari pendaftaran pasien, pengolahan data rekam medis, audit isi rekam medis, pengarsipan/pengelolaan rekam medis serta penyajian informasi rekam medis. Pengelolaan rekam medis yang buruk dapat menyebabkan mutu pelayanan menjadi buruk. Klinik Khalifah merupakan klinik swasta yang melayani 24 jam pengobatan persalinan, dikelola oleh perseorangan yang berlokasi di Teluk Naga, Kabupaten Tangerang, Banten. Tujuan pengabdian ini adalah merevitalisasi sistem pengelolaan rekam medis di Klinik Khalifah yaitu dengan menentukan dan membuat sistem penomoran, sistem penamaan, sistem penyimpanan dan sistem penjajaran rekam medis yang efektif dan efisien. Berdasarkan hasil pengabdian masyarakat revitalisasi sistem pengelolaan rekam medis di Klinik Khalifah Ã‚Â diantara adalah sistem pengarsipan desentralisasi diubah menjadi sentralisasi, proses pendaftaran secara manual menjadi elektronik, sistem penomoran dengan unit numbering system dengan 6 digit, sistem penomoran dapat dijadikan family numbering, sistem penamaan dengan nama langsung (sesuai KTP), sistem penjajaran dari nomor langsung menjadi terminal digit filing / sistem angka akhir.Ã‚Â Kata kunci:Ã‚Â pengelolaan, rekam medis, klinik